Strategi Inovasi Produk Keuangan Syariah untuk Meningkatkan Inklusi Finansial - Ainun Nufus; Natasya Natasya; Mas Munfasiroh; Rasidah Novita Sari (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to analyze strategies for product innovation in Islamic finance to enhance financial inclusion, a significant challenge in countries with large Muslim populations such as Indonesia. The research employs a qualitative approach, utilizing data from various literature sources, including academic journal articles, reports from Islamic financial institutions, and government regulations. The findings reveal that Islamic financial product innovation can be categorized into new product development, digital technology adoption, improvement of Islamic financial literacy, and cross-sectoral collaboration. Products such as microfinance based on Sharia contracts, digital waqf savings, and technology-driven Takaful insurance exemplify innovations aligned with modern societal needs. Additionally, Islamic fintech platforms have expanded financial access for remote communities, despite challenges such as low digital literacy and limited infrastructure. Islamic financial literacy emerges as a crucial element influencing public trust and participation in formal financial systems. In practice, cross-sector collaboration among Islamic financial institutions, governments, and the technology sector serves as a strategic approach to address regulatory barriers, competition with conventional sectors, and inconsistent global standards. This study recommends strengthening regulations, enhancing financial literacy, developing inclusive digital technologies, and fostering international cooperation to support the sustainable growth of the Islamic finance sector. With integrated strategies, Islamic finance holds significant potential not only to improve financial inclusion but also to create a fairer, more inclusive financial system that aligns with Islamic values in the modern era.